Multimodal Imaging Markers of Cognitive Resilience and Molecular Mechanisms of Brain Resilience in Alzheimer’s Disease - Ze Yang; Jinhua Sheng; Qiao Zhang; Xiaoying Zhao; Yan Song; Guiguan Dong; Rong Zhang; Hongliang Zhao; Jialei Wang; Rong Pan; Haodi Zhu (Journal of Integrative Neuroscience)
Owing to the intricacy of the dementia course and the selection of clinical trial populations, research on distinct populations, comorbid conditions, and disease heterogeneity is currently a topic of great interest. For instance, more than 30% of individuals enlisted for natural history and clinical trial studies may exhibit pathology extending beyond Alzheimer’s disease (AD). Additionally, recent autopsy studies have evinced significant heterogeneity in the neuropathology of individuals who succumb to dementia, with approximately 10%–30% of those clinically diagnosed with AD revealing no neurological lesions at autopsy. Nevertheless, 30%–40% of cognitively intact elderly individuals exhibit neurological lesions at autopsy. This indicates that the brain can withstand accumulated aging and neurological lesions while retaining brain integrity (brain resilience) or cognitive function (cognitive resilience). Presently, there is a lack of consensus on how to precisely define and measure the resilience of the brain and cognitive decline. This article encapsulates the research on constructing multimodal neuroimaging biomarkers for cognitive resilience, summarizes existing methods, and proposes some improvements. Furthermore, research findings on the biological mechanisms and genetic traits of brain resilience were collated, and the mechanisms for the formation of resilience and the genetic loci governing it were elucidated. Potential future research directions are also discussed.